Study of the Usability Testing of E-Commerce Applications. Issue 4 (July 2021) - Jain, Samkit; Purandare, Pradnya
Abstract: Usability Testing determines the friendliness of the application to meet customers' requirements. It must be adopted in the early stage of SDLC (Software Development Life Cycle) to avoid issues in a later stage. Today, E-commerce has revolutionized the mode of shopping, and thus, we need to focus on ways to improve the usability of e-commerce applications. We opted for survey questionnaires as our research methodology, along with testing websites using online tools based on the four parameters Connectivity, Readability, Accessibility, and Functional Performance. In the survey, the four most popular e-commerce applications were Amazon, Flipkart, Bigbasket, and Paytm. Out of which, Amazon was the most used e-commerce application by the consumers. Although, testing tools are depicted that applications need to improve in certain areas. From the analysis, we concluded that consumers are aware of the upcoming Jio-Mart, which can give tough competition to existing companies. Thus, all the existing e-commerce companies need to improve their web and mobile applications to retain their customer base.